A New Penthrite Grenade Compared to the Traditional Black Powder Grenade: Effectiveness in the Alaskan Eskimos' Hunt for Bowhead Whales - Øen, Egil Ole (ARCTIC, 1995)
The Alaskan Eskimos catch bowhead whales of the protected Bering-Chukchi-Beaufort Sea stock using old-fashioned weapons and grenades filled with black powder. Killing is sometimes a lengthy process, and in some years relatively large numbers of animals are lost. A new grenade containing the explosive penthrite was developed for the Eskimos' traditional weapons and first tested in the bowhead whale hunt in 1988, when eight whales were killed by penthrite grenades. Seven of these were landed, and one dead whale was lost. Five whales died instantaneously or within five minutes. Tissue and organ damage was inspected by post-mortem examination. Although data collected after 1988 are less reliable, the survival times recorded for animals landed up to 1992 were markedly shorter for the penthrite grenade than for the traditional black powder grenade. Median survival times were 62 minutes for whales killed by black powder grenades and 15 minutes for those killed by penthrite grenades; 21% and 45% of the animals, respectively, were recorded as dead within five minutes, and 32% and 19% respectively, were lost. The penthrite grenade is likely to become a highly effective weapon for the bowhead whale hunt, although further modification and testing will be needed before large-scale use. An educational and training programme for all prospective users should also be arranged. The possibility of improving other catch equipment to reduce whale loss should also be considered.Key words: bowhead whale, Balaena mysticetus, Eskimo traditional subsistence hunt, Alaska, hunting method, black powder grenade, penthrite grenade Les Eskimos de l'Alaska chassent la baleine boréale de la population protégée des mers de Béring, des Tchouktches et de Beaufort au moyen d'armes à l'ancienne et de grenades remplies de poudre noire. Il faut parfois beaucoup de temps pour tuer l'animal, et certaines années un nombre relativement élevé d'animaux sont perdus. Une nouvelle grenade contenant de la pentrite a été mise au point pour les armes ...